Journal of biomimetics, biomaterials and biomedical engineering. Vol. 53. (Journal of Biomimetics, Biomaterials and Biomedical Engineering Ser., 2021)
The idea of this special edition was the combination of scientific works on topics of actual problems of biomimetics and scientific approaches to the creation of biocompatible implant materials used in implantology. Comprehensive information about actual issues of biomedical engineering as a modern component of science in biology and medicine is provided. The interdisciplinary approach of biomedical engineering in the development of technical devices for medical research is reasoned. Clinical scientific works dedicated to the treatment of patients of Clinic of Traumatology and Orthopedics with the Hallux Valgus pathology as well as the research that illustrates the histological features of osteoarthritis in a state of decompensation are provided for your attention. The work of neurologists that reveals the biological significance of facial ganglia lesions from the fundamental positions of anatomy and symptomology is also presented. Biomimetics, Biomedical Engineering, Implantology, Biocompatibility, Osteotomy, Dental Materials, Musculoskeletal System, Osteoarthritis Materials Science, Bioscience and Medicine, Mechanics.